FILSAFAT PENDIDIKAN MENURUT PERSPEKTIF JAWA (Studi Pemikiran Ki Hajar Dewantara) - Nurkholida, Erna (IAIN Ponorogo, 2018)
Teaching in new civilization is more complicated than many years ago. On the one side teacher should prepare studentsâ skill to face their future, however teacher should also build studentsâ characters. The teacherâs task to develop those purposes is more complicated. One of the most current issues to deal with such phenomena is to ferret out the teaching strategy that is able to enhance the teachersâ ability as well as to reinforce their role in teaching by maximizing the use of heart, brain and sense. In response to such issues, this paper takes into account teaching by heart as a strategy and elaborates the theoretical review of teaching by heart for better understanding. Areas of potential future research regarding the impact of the development of inner value into pedagogical field also are highlighted.Ø§ÙØªØ¹ÙÙÙ ÙÙ Ø§ÙØØ¶Ø§Ø±Ø© Ø§ÙØ¬Ø¯ÙØ¯Ø© Ø£ÙØ«Ø± ØªØ¹ÙÙØ¯ÙØ§ Ù Ù Ø³ÙÙØ§Øª Ø¹Ø¯ÙØ¯Ø© Ù Ø¶Øª. ÙÙ Ø¬Ø§ÙØ¨ ÙØ§ØØ¯Ø ÙØ¬Ø¨ Ø¹ÙÙ Ø§ÙÙ Ø¹ÙÙ Ø¥Ø¹Ø¯Ø§Ø¯ Ù ÙØ§Ø±Ø© Ø§ÙØ·ÙØ§Ø¨ ÙÙ ÙØ§Ø¬ÙØ© Ù Ø³ØªÙØ¨ÙÙÙ Ø ÙÙÙÙ ÙØ¬Ø¨ Ø¹ÙÙ Ø§ÙÙ Ø¹ÙÙ Ø£ÙØ¶ÙØ§ Ø¨ÙØ§Ø¡ Ø´Ø®ØµÙØ§Øª Ø§ÙØ·ÙØ§Ø¨. Ù ÙÙ Ø© Ø§ÙÙ Ø¹ÙÙ ÙØªØ·ÙÙØ± ÙØ°Ù Ø§ÙØ£ØºØ±Ø§Ø¶ Ø£ÙØ«Ø± ØªØ¹ÙÙØ¯ÙØ§. ÙØ§ØØ¯Ø© Ù Ù Ø£ÙØ«Ø± Ø§ÙÙØ¶Ø§ÙØ§ Ø§ÙØØ§ÙÙØ© ÙÙØªØ¹Ø§Ù Ù Ù Ø¹ Ù Ø«Ù ÙØ°Ù Ø§ÙØ¸ÙØ§ÙØ± ÙÙ Ø§ÙÙØ´Ù Ø¹Ù Ø§Ø³ØªØ±Ø§ØªÙØ¬ÙØ© Ø§ÙØªØ¯Ø±ÙØ³ Ø§ÙÙØ§Ø¯Ø±Ø© Ø¹ÙÙ ØªØ¹Ø²ÙØ² ÙØ¯Ø±Ø© Ø§ÙÙ Ø¹ÙÙ ÙÙ ÙÙØ°ÙÙ ÙØªØ¹Ø²ÙØ² Ø¯ÙØ±ÙÙ ÙÙ Ø§ÙØªØ¯Ø±ÙØ³ Ù Ù Ø®ÙØ§Ù ØªØ¹Ø¸ÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙÙÙØ¨ ÙØ§ÙØ¯Ù Ø§Øº ÙØ§ÙØØ³. Ø§Ø³ØªØ¬Ø§Ø¨Ø© ÙÙØ°Ù Ø§ÙÙØ¶Ø§ÙØ§Ø ØªØ£Ø®Ø° ÙØ°Ù Ø§ÙÙØ±ÙØ© Ø¨Ø¹ÙÙ Ø§ÙØ§Ø¹ØªØ¨Ø§Ø± Ø§ÙØªØ¯Ø±ÙØ³ Ø¹Ù Ø¸ÙØ± ÙÙØ¨ ÙØ§Ø³ØªØ±Ø§ØªÙØ¬ÙØ© ÙØªØ´Ø±Ø Ø§ÙÙ Ø±Ø§Ø¬Ø¹Ø© Ø§ÙÙØ¸Ø±ÙØ© ÙÙØªØ¹ÙÙÙ Ø¨Ø§ÙÙÙØ¨ Ù Ù Ø£Ø¬Ù ÙÙÙ Ø£ÙØ¶Ù. ÙÙ Ø§ ØªÙ ØªØ³ÙÙØ· Ø§ÙØ¶ÙØ¡ Ø¹ÙÙ Ù Ø¬Ø§ÙØ§Øª Ø§ÙØ£Ø¨ØØ§Ø« Ø§ÙÙ Ø³ØªÙØ¨ÙÙØ© Ø§ÙÙ ØØªÙ ÙØ© Ø§ÙÙ ØªØ¹ÙÙØ© Ø¨ØªØ£Ø«ÙØ± ØªØ·ÙØ± Ø§ÙÙÙÙ Ø© Ø§ÙØ¯Ø§Ø®ÙÙØ© ÙÙ Ø§ÙÙ Ø¬Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ.